1
$\begingroup$

I'm reading about k-forms right now but am still quite confused about the different notations, which is why I'm trying to look at a concrete example. Let's say we have a one-form in three-dimensions: $\omega(x) = dx + 2dy - 4dz$, and for example the vector $\vec{a} = (1,1,1)$, how would I compute $\omega(\vec{a})$? Is that a reasonable question to ask? Sorry if it's confusing, but I'm really just trying to make sense of this by self study which is quite hard.

$\endgroup$
1
  • 1
    $\begingroup$ You might find my YouTube lectures helpful. Note that there is a complete version of the first differential forms lecture at the very bottom of the long list. $\endgroup$ Dec 9 '19 at 20:27
1
$\begingroup$

If your form is $\omega = \,dx + 2 \,dy - 4 \,dz$ and your tangent vector at the point $a$ is $t_a = (1,1,1)$, then you can think about each of the $\,dx, \,dy, \,dz$ as projecting onto the corresponding components of the tangent vector.

In your example, \begin{align*} \omega(t_a) &= \,dx(1,1,1) + 2 \cdot \,dy (1,1,1) - 4 \,dz(1,1,1) \\ &= 1 + 2 \cdot 1 - 4 \cdot 1 \\ &= -1 \end{align*}

Let's look at another example. If your point is $a = (1,2,3)$ and your tangent vector at $a$ is $t_a = (3,2,1)$ and we define $\omega = x \,dx + 2y^2 \,dy - 3xz \,dz$, then \begin{align*} \omega(t_a) &= 1 \,dx (3,2,1) + 2(2)^2 \,dy(3,2,1) - 3 \cdot 1 \cdot 3 \,dz (3,2,1) \\ &= 1 \cdot 3 + 8 \cdot 2 - 9 \cdot 1 \\ &=10. \end{align*}

$\endgroup$
3
  • $\begingroup$ Thanks for that really quick and great answer. Since I can't seem to find an example that basic, could you also tell me how I would wedge the two $\omega_1$ and $\omega_2$ from above? $\endgroup$
    – MJP
    Dec 9 '19 at 22:04
  • 1
    $\begingroup$ Sure thing: note that $\,dx \wedge \,dx = 0$. Then with $\omega_1 = \,dx + 2 \,dy - 4 \,dz$ and $\omega_2 = x \,dx + 2y^2 \,dy - 3xz \,dz$, we have: $\omega_1 \wedge \omega_2 = x \,dx \wedge \,dx + 2x \,dy \wedge \,dx - 4x \,dz \wedge \,dx + 2y^2 \,dx \wedge \,dy + 4y^2 \,dy \wedge \,dy - 8y^2 \,dz \wedge \,dy - 3xz \,dx \wedge \,dz - 6xz \,dy \wedge \,dz + 12xz \,dz \wedge \,dz$. $\endgroup$
    – Alvin Jin
    Dec 9 '19 at 22:15
  • $\begingroup$ Thanks, great help. $\endgroup$
    – MJP
    Dec 9 '19 at 22:17

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.